Antimicrobial and Antioxidant Properties of Bovine Livers and Hearts Hydrolysates - Ignė Juknienė; Gintarė Zaborskienė; Agnė Jankauskienė; Irena Mačionienė (Applied Sciences, 2023)
Our previous research has indicated that bioactive protein hydrolysates derived from porcine by-products possess the potential to be utilized in the production of functional additives and food supplements. The objective of this investigation was to assess the antioxidant and antimicrobial characteristics and amino acid changes in hydrolysates of lyophilized meat of bovine livers and hearts. The relevant enzymes, papain and pepsin, were used to hydrolyze the meat by-products over periods of 3, 6, and 24 h. The antimicrobial properties of all enzymatically digested samples were assessed against Listeria monocytogenes, Bacillus cereus, Salmonella enterica subsp. enterica Serovar Typhimurium. Bacillus cereus, and Escherichia coli, S. aureus subsp. aureus. The assessment of antiradical activity involved the quantification of DPPH• and ABTS•+ absorbance in bovine by-product hydrolysates. The hydrolysates were subjected to amino acid analysis using AccQ Tag technology, which was performed by Waters Corporation in Milford, MA, USA. The bacteria L. monocytogenes had the highest antibacterial activity (inhibition zone) (20.00 ± 0.20 mm) and less against E. coli (10.00 ± 0.10 mm) of bovine heart hydrolysates and were prepared for 24 h with papain. The highest values of ABTS•+ (98.1 ± 0.30%) and of DPPH• scavenging activity (92.56 ± 0.56%) of cationic radicals were evaluated in the bovine liver hydrolysates after the effect of papain for 24 h. Longer hydrolysis time influenced the decrease in free hydrophobic amino acids (Ala, Val, Ile, Leu, Tyr, Phe, Pro, Met). The results confirmed the potential use of bovine liver and heart hydrolysates as functional or biologically active materials.